Misinformation regulations: early evidence on corporate social media strategy - Crowley, Richard M.; Lou, Yun; Tan, Samuel T.; Zhang, Liandong (Review of Accounting Studies, 2025)
Against the backdrop of an increasing threat of misinformation on social media, several countries have enacted regulations to curb the spread of misinformation. This study examines how corporate social media strategy responds to misinformation regulations. Using a large cross-country dataset of corporate tweets and a stacked regression analysis, we show that misinformation regulations lead to less corporate social media disclosure. This result suggests that, by deterring misinformation, these regulations reduce firms’ need to use social media to counteract its adverse effects. Additional analyses show that the effect strengthens among countries with higher social media usage and those with stronger investor protection but weakens for firms with stronger information environments. Finally, we provide direct evidence that firms post fewer tweets refuting misinformation about themselves following the enactment of these regulations.